Rapid degradation of zinc oxide nanoparticles by phosphate ions - Herrmann, Rudolf; García-García, F. Javier; Reller, Armin (Beilstein Journal of Nanotechnology, 2014)
Zinc oxide nanoparticles are highly sensitive towards phosphate ions even at pH 7. Buffer solutions and cell culture media containing phosphate ions are able to destroy ZnO nanoparticles within a time span from less than one hour to one day. The driving force of the reaction is the formation of zinc phosphate of very low solubility. The morphology of the zinc oxide particles has only a minor influence on the kinetics of this reaction. Surface properties related to different production methods and the presence and absence of labelling with a perylene fluorescent dye are more important. Particles prepared under acidic conditions are more resistant than those obtained in basic or neutral reaction medium. Surprisingly, the presence of a SiO2 coating does not impede the degradation of the ZnO core. In contrast to phosphate ions, β-glycerophosphate does not damage the ZnO nanoparticles. These findings should be taken into account when assessing the biological effects or the toxicology of zinc oxide nanoparticles.
Keywords: degradation; phosphate; silica shell; zinc oxide nanoparticles; zinc phosphate

(untitled) - Djurišić, A. B.; Leung, Y. H. (Small, 2006)

(untitled) - Servais, G. E.; Cartz, L. (J. Dent. Res., 1971)

(untitled) - Awad, S. A.; Kamel, K. M. (J. Electroanal. Chem., 1970)

(untitled) - Dupuis, V.; Laviole, O.; Potin-Gautier, M.; Castetbon, A.; Moya, F. (Biomaterials, 1992)

(untitled) - Sugama, T.; Takahasi, T. (J. Mater. Sci., 1995)

(untitled) - Ziemniak, S. E.; Opalka, E. P. (Chem. Mater., 1994)

(untitled) - Ziemniak, S. E.; Jones, M. E.; Combs, K. E. S. (J. Solution Chem., 1992)

(untitled) - Michelmore, A.; Jenkins, P.; Ralston, J. (Int. J. Miner. Process., 2003)

(untitled) - Tso, C.-p.; Zhung, C.-m.; Shih, Y.-h.; Tseng, Y.-M.; Wu, S.-c.; Doong, R. a. (Water Sci. Technol., 2010)

(untitled) - Ali, M.; Winterer, M. (Chem. Mater., 2010)

(untitled) - Franklin, N. M.; Rogers, N. J.; Apte, S. C.; Batley, G. E.; Gadd, G. E.; Casey, P. S. (Environ. Sci. Technol., 2007)

(untitled) - Jiang, W.; Mashayekhi, H.; Xing, B. (Environ. Pollut. (Oxford, U. K.), 2009)

(untitled) - Peng, X.; Palma, S.; Fisher, N. S.; Wong, S. S. (Aquat. Toxicol., 2011)

(untitled) - Gilbert, B.; Fakra, S. C.; Xia, T.; Pokhrel, S.; Mädler, L.; Nel, A. E. (ACS Nano, 2012)

(untitled) - Miao, A.-J.; Zhang, X.-Y.; Luo, Z.; Chen, C.-S.; Chin, W.-C.; Santschi, P. H.; Quigg, A. (Environ. Toxicol. Chem., 2010)

(untitled) - Bian, S.-W.; Mudunkotuwa, I. A.; Rupasinghe, T.; Grassian, V. H. (Langmuir, 2011)

(untitled) - Mudunkotuwa, I. A.; Rupasinghe, T.; Wu, C.-M.; Grassian, V. H. (Langmuir, 2012)

(untitled) - Mortimer, M.; Kasemets, K.; Kahru, A. (Toxicology, 2010)

(untitled) - Li, M.; Zhu, L.; Lin, D. (Environ. Sci. Technol., 2011)

(untitled) - Baek, Y.-W.; An, Y.-J. (Sci. Total Environ., 2011)

(untitled) - Xia, T.; Kovochich, M.; Liong, M.; Mädler, L.; Gilbert, B.; Shi, H.; Yeh, J. I.; Zink, J. I.; Nel, A. E. (ACS Nano, 2008)

(untitled) - Reed, R. B.; Ladner, D. A.; Higgins, C. P.; Westerhoff, P.; Ranville, J. F. (Environ. Toxicol. Chem., 2012)

(untitled) - Misra, S. K.; Dybowska, A.; Berhanu, D.; Luoma, S. N.; Valsami-Jones, E. (Sci. Total Environ., 2012)

(untitled) - Lv, J.; Zhang, S.; Luo, L.; Han, W.; Zhang, J.; Yang, K.; Christie, P. (Environ. Sci. Technol., 2012)

(untitled) - Wang, J.; Tsuzuki, T.; Sun, L.; Wang, X. (J. Am. Ceram. Soc., 2009)

(untitled) - Blechinger, J.; Herrmann, R.; Kiener, D.; García-García, F. J.; Scheu, C.; Reller, A.; Bräuchle, C. (Small, 2010)

(untitled) - Dentani, T.; Funabiki, K.; Jin, J. Y.; Yoshida, T.; Minoura, H.; Matsui, M. (Dyes Pigm., 2007)

(untitled) - Demir, M. M.; Muñoz-Esqui, R.; Lieberwirth, I.; Wegner, G. (J. Mater. Chem., 2006)

(untitled) - Sun, D.; Wong, M.; Sun, L.; Li, Y.; Miyatake, N.; Sue, H.-J. (J. Sol-Gel Sci. Technol., 2007)

(untitled) - Mahmud, S.; Abdullah, M. J.; Putrus, G. A.; Chong, J.; Mohamad, A. K. (Synth. React. Inorg., Met.-Org., Nano-Met. Chem., 2006)

(untitled) - Rathje, W. (Ber. Dtsch. Chem. Ges., 1941)

(untitled) - David, C. A.; Galceran, J.; Rey-Castro, C.; Puy, J.; Companys, E.; Salvador, J.; Monné, J.; Wallace, R.; Vakourov, A. (J. Phys. Chem. C, 2012)

(untitled) - Turney, T. W.; Duriska, M. B.; Jayaratne, V.; Elbaz, A.; O'Keefe, S. J.; Hastings, A. S.; Piva, T. J.; Wright, P. F. A.; Feltis, B. N. (Chem. Res. Toxicol., 2012)

(untitled) - Cheng, C.; Xin, R.; Leng, Y.; Yu, D.; Wang, N. (Inorg. Chem., 2008)

(untitled) - Han, K.; Zhao, Z.; Xiang, Z.; Wang, C.; Zhang, J.; Yang, B. (Mater. Lett., 2007)

(untitled) - Lettinga, M. P.; van Zandvoort, M. A. M. J.; van Kats, C. M.; Philipse, A. P. (Langmuir, 2000)

(untitled) - Dembski, S.; Graf, C.; Krüger, T.; Gbureck, U.; Ewald, A.; Bock, A.; Rühl, E. (Small, 2008)

(untitled) - Lin, W.; Xu, Y.; Huang, C.-C.; Ma, Y. F.; Shannon, K. B.; Chen, D.-R.; Huang, Y.-W. (J. Nanopart. Res., 2009)

(untitled) - Tsou, T.-C.; Yeh, S.-C.; Tsai, F.-Y.; Lin, H.-J.; Cheng, T.-J.; Chao, H.-R.; Tai, L.-A. (J. Hazard. Mater., 2010)

(untitled) - Wang, H.; Wingett, D.; Engelhard, M. H.; Feris, K.; Reddy, K. M.; Turner, P.; Layne, J.; Hanley, C.; Bell, J.; Tenne, D.; Wang, C.; Punnoose, A. (J. Mater. Sci.: Mater. Med., 2009)